Flow Characteristics and Pressure‐Compensating Mechanism of Non‐Pressure‐Compensating Drip Irrigation Emitters1. (19th November 2015) - Zhangzhong, Lili; Yang, Peiling; Ren, Shumei; Liu, Yu; Li, Yunkai
Abstract: The flow regime index ( x ) is a key parameter for evaluation of the drip irrigation capacity of emitters. Developing an emitter with low x has become the goal for numerous emitter developers. Currently, the phenomenon shows that the x of some non‐pressure‐compensating (non‐PC) drip irrigation emitters are less than 0.5, which cannot be easily explained by the macro‐pipeline hydraulic principle. Therefore, in this paper, we adopted the standard k–ε model to calculate and analyse the internal flow field of four non‐PC emitters (with x all less than 0.5). The results indicated that the flow fields within these flow paths had obvious self‐compensating effects. It showed that when work pressure increased, the flow characteristics changed correspondingly: the area of the low‐speed vortex region expanded incrementally, resulting in shrinkage of the width of the flow cross‐section in the high‐speed mainstream region, also inhibiting the increments of emitter outflow rates and alleviating the influence of pressure variation on outflow raters, and finally reducing the value of x . When the pressure increased from 10 to 150 kPa, the maximum shrinkage of flow cross‐section ( R max, the flow cross‐section shrinkage rate under the work pressure, increased from 10 to 150 kPa) of emitters S1, M1, M2 and M3 was 32.0, 16.4, 13.8 and 10.3%, respectively. R max had a significantly negative linear relationship with x . As R max increased, the adjustment range of the flow cross‐section became greater and sensitivity of the regulating flow improved. Then the x of the non‐PC emitter declined, indicating higher self‐compensating capacity of the emitter. Copyright © 2015 John Wiley & Sons, Ltd.